Robust power and subcarrier allocation algorithm for cognitive network based on interference efficiency maximization - Yongjun XU; Yang YANG; Qilie LIU; Qianbin CHEN; Jinzhao LIN (Tongxin xuebao)
For the cognitive OFDMA uplink communication system,a robust power and subcarrier allocation algorithm based on maximum interference efficiency was proposed.Firstly,considering primary user interference constraint,secondary user transmit power constraint,subcarrier allocation constraint and secondary user minimum rate constraint,a robust resource optimization model based on outage probability was established.Then,by using Bernstein approximation and Dinkelbach’s method,the original non-convex problem based on outage probability was transformed into an equivalent convex optimization one,and the analytical solution was obtained by Lagrangian dual function method.Meanwhile,the computational complexity and robust sensitivity of the algorithm were analyzed.The simulation results show that the proposed algorithm has better interference efficiency and robustness.